Broodstock nutrition in Nile tilapia and its implications on reproductive efficiency - Engdaw, Flipos; Geremew, Akewake (Frontiers in Aquaculture, 2024)
Broodstock nutrition is the most essential constituent of sustainable aquaculture production. Its impact on the reproductive performance and profitability of commercial aquaculture has been the subject of considerable research. The present paper reviews the literature available on the subject, examining the implication of Nile tilapia broodstock nutrition on parameters including maturation, fecundity, fertilization, embryo development, larval quality, and survival rate. The provision of a nutritive diet composed of essential macro- and micronutrients including proteins, lipids, carbohydrates, vitamins, minerals, and functional additives, such as prebiotics, enzymes, hormones, and probiotics, in different proportions is discussed. Special emphasis is given to literature dealing with the effects of dietary protein and lipid on vitellogenesis and ovarian maturation, fecundity, egg hatching rate, larval quality, and fry survival number. The impact of the feeding regime on reproductive performance is described.